2020
DOI: 10.1289/ehp6627
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Ability of Developmentally Precocious Estrogen Signaling to Recapitulate Ovarian Transcriptomes and Follicle Dynamics in Alligators from a Contaminated Lake

Abstract: Background: Concern has grown in recent decades over anthropogenic contaminants that interfere with the functioning of endocrine hormones. However, mechanisms connecting developmental processes to pathologies associated with endocrine-disrupting chemical (EDC) exposure are poorly understood in naturally exposed populations. Objectives: We sought to a ) characterize divergence in ovarian transcriptomic and follicular profiles between alligators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…However, in this study and others, EDCs typically exhibit weak agonism of nuclear estrogen receptors, with activation on par with E2 only observed at high concentrations [Vonier et al, 1996;Bolger et al, 1998;Guillette et al, 2002]. Interestingly, when alligator eggs collected from a reference lake are treated with E2 prior to the start of ovarian estrogen synthesis (measured by CYP19A1 expression), the ovarian transcriptome in resulting juvenile alligators broadly mirrors those measured in alligators from Lake Apopka [Hale et al, 2019;Hale and Parrott, 2020]. Additionally, impediments to folliculogenesis observed in ovaries of Lake Apopka alligators, including severe decreases in stage III follicles and increases in germ cell nests were also induced by embryonic treatment with E2 [Hale and Parrott, 2020].…”
Section: Xenopus Laevissupporting
confidence: 56%
See 1 more Smart Citation
“…However, in this study and others, EDCs typically exhibit weak agonism of nuclear estrogen receptors, with activation on par with E2 only observed at high concentrations [Vonier et al, 1996;Bolger et al, 1998;Guillette et al, 2002]. Interestingly, when alligator eggs collected from a reference lake are treated with E2 prior to the start of ovarian estrogen synthesis (measured by CYP19A1 expression), the ovarian transcriptome in resulting juvenile alligators broadly mirrors those measured in alligators from Lake Apopka [Hale et al, 2019;Hale and Parrott, 2020]. Additionally, impediments to folliculogenesis observed in ovaries of Lake Apopka alligators, including severe decreases in stage III follicles and increases in germ cell nests were also induced by embryonic treatment with E2 [Hale and Parrott, 2020].…”
Section: Xenopus Laevissupporting
confidence: 56%
“…Bisphenol A BPA Kloas et al, 1999;Levy et al, 2004 Xenopus laevis Nonlyphenol Surfactant Kloas et al, 1999 Xenopus [Silurana] tropicalis 17α-ethinylestradiol Synthetic hormone Pettersson et al, 2006;Pettersson and Berg, 2007;Berg et al, 2009;Gyllenhammar et al, 2009a,b;Hirakawa et al, 2013 Xenopus [Silurana] licles and polyovular follicles, were first reported in juvenile alligators inhabiting the lake [Guillette et al, 1994]. Subsequent studies using a combination of field collections and lab incubations revealed that disruptions in steroidogenic and TGF-β signaling pathways along with impeded folliculogenesis occurring in juvenile ovaries likely stemmed from earlier embryonic exposure due to the maternal deposition of these contaminants in yolks [Moore et al, 2010b[Moore et al, , 2011[Moore et al, , 2012bHale et al, 2019;Hale and Parrott., 2020]. Altogether, these and other reports from Lake Apopka suggest that embryonic exposure to EDCs alters transcriptional networks involved in early oogenesis and folliculogenesis and that these perturbations persist into juvenile life and perhaps beyond.…”
Section: Xenopus Laevismentioning
confidence: 99%
“…Additionally, alligators are long‐lived apex predators and maternal deposition of common environmental contaminants into yolk, such as 1,1′‐(2,2‐dichloroethene‐1,1‐dyl)bis(4‐chlorobenzene) ( p , p ′‐DDE), referred to from here forward as DDE, alters reproductive development and subsequent function in offspring (Crain et al, 1997; Guillette, 1994; Hale et al, 2019; Moore et al, 2010). While disrupted oestrogen signalling appears to underlie many of the observed reproductive abnormalities (Hale et al, 2019; Hale & Parrott, 2020), DDE has the potential to affect additional endocrine pathways as well as other cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…Dichlorodiphenyltrichloroethane (DDT) is a widespread and persistent organochlorine pesticide, and its primary metabolite, dichlorodiphenyldichloroethylene (DDE), is capable of disrupting androgen signaling (Kelce et al, 1995). Impaired reproductive function is associated with EDC exposure (including elevated levels of DDE) in a wild alligator population in Florida (Guillette et al, 1994(Guillette et al, , 1999, and experimental work has demonstrated that these alterations to reproductive function originate during development (Moore et al, 2012;Hale et al, 2019;Hale and Parrott, 2020). In laboratory studies, in ovo exposure to DDE induces female-biased sex ratios in turtles and alligators (Willingham and Crews, 1999;Milnes et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%